2017
DOI: 10.18203/2320-6012.ijrms20174966
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its associated factors among medical students: a study using beck depression inventory

Abstract: Background: Medical education carries with it a great burden of stress that can result in depression. This study was conducted to assess the prevalence of depression in medical students and various factors contributing to depression in the institute.Methods: A stratified random sample of 280 students was evaluated using Beck Depression Inventory by investigators. Associations between depression and year of study, addiction like alcohol use, family problems, family history of depression and staying away from ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In a study in India, majority 69.9% were adjudged normal, 6.4% had moderate depression while the least proportion, 0.7% had very severe depression. [27] The result from a study in Malaysia is however different in which 45% were normal while 13.5% had moderate depression. [29] In another study in Egypt, 19.5% were normal while 24.4% had moderate depression.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a study in India, majority 69.9% were adjudged normal, 6.4% had moderate depression while the least proportion, 0.7% had very severe depression. [27] The result from a study in Malaysia is however different in which 45% were normal while 13.5% had moderate depression. [29] In another study in Egypt, 19.5% were normal while 24.4% had moderate depression.…”
Section: Discussionmentioning
confidence: 95%
“…[20] A higher proportion of students than was obtained in this study were found to be depressed in other studies involving medical students in Africa [21,22,23] as well as other studies outside Africa. [24][25][26][27][28][29] Also, higher proportion of medical students were reported depressed from systematic reviews. [6,7] Based on these observations, a study concluded on the importance of initiating stress management strategies among medical students as a way of preventing depression among the students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation